Zinc(II) and cobalt(II) complexes with unusual coordination of mixed imidazole-1, 2, 4-triazole ligand in a protonated cationic form. (1st May 2022) - Yu, Xiaolin; Gao, Enjun; Yao, Wei; Fedin, Vladimir P.; Potapov, Andrei S.
Graphical abstract: Zinc(II) and cobalt(II) molecular coordination compounds with the mixed-donor 1-(4-(1H-imidazol-1-yl)benzyl)-1H-1, 2, 4-triazole were prepared, their crystal structures were determined by single-crystal X-ray structure analysis. The ligand is coordinated in a protonated form at imidazole nitrogen atom, thus the compounds represent rare examples of metal coordination compounds with the cationic ligands. Abstract: Zinc(II) and cobalt(II) molecular coordination compounds with the mixed-donor 1-(4-(1H-imidazol-1-yl)benzyl)-1 H -1, 2, 4-triazole were prepared and their crystal structure was determined by single crystal X-ray diffraction analysis. Both metal cations are in a slightly distorted tetrahedral arrangement, the heterocyclic ligand is coordinated via 1, 2, 4-triazole nitrogen atoms at position 4 of the ring, consistent with the localization of a negative charge at this atom, according to DFT calculations. Upon coordination, the ligand undergoes protonation with the formation of rare examples of transition metal coordination compounds with the cationic ligands. Zinc(II) complex demonstrated ligand-centered photoluminescence with the maximum near 302 nm upon excitation at 264 nm.